INVESTIGATING PRE-SERVICE TEACHERS’ SELF-AWARENESS OF PROFESSIONAL DEVELOPMENT - Zehan A. Ainussamsi; Bilal Mohnawawi; Firda Fauziyah; Imelia N. Nafisah (Siliwangi University, 2018)
Psychologically, self-awareness has been stated as one of the indicators of emotional intelligence. Plenty of previous studies have already discussed students’ and teachers' awareness. However, many of them were not concerning the field of professional development, especially for the pre-service language teacher. A professional development itself is an aspect that could not be neglected since professionalism is necessary to reach a good teaching-learning quality. Therefore, the present study seeks to investigate the existence of self-awareness among the non-native pre-service language teachers toward their professional development. The data obtained from an open-ended interview is processed qualitatively and analyzed thematically. Within this regard, self-awareness of their professional development would be examined, analyzed and described. Furthermore, the requirements and suggestions for the professional development in which how non-native pre-service language teacher education program in an EFL context might have to be discussed. The result of the study would be discussed further in this paper.